Unemployment duration and labor mobility in Argentina: a socioeconomic-based pre and post-crisis analysis - Canavire-Bacarreza, Gustavo Javier (2007)
This paper evaluates the unemployment duration and labor mobility using data from the household surveys provided by the National Statistical office (INDEC) for the period 1998 to 2005. The paper aims to understand and explain the evolution and main determinants of labor mobility and unemployment duration, two of the main problems that labor markets present. Unemployment duration is studied in terms of welfare and its determinants by applying stochastic dominance and econometric techniques. Labor mobility is analyzed using conditional multinomial probit techniques in order to evaluate its evolution, the impact of a crisis and the recovery period, that Argentina faced over the period 1998-2005. We found that there was deterioration in welfare measured by unemployment duration especially during the crisis period. We found that human capital played a key role in the unemployment duration and labour mobility. Unemployment duration is higher for people with higher educational levels, which shows that less educated people have lower reservations wages; similar result was found for females and males. The labour mobility results show that more educated people enter easier to formal labor markets which changes during the crisis when their probability of entering to formal labor market reduces; this would suggest that more educated people tend to adjust their wages and push out of the market less educated people. The labour mobility patterns do not reflect inflexibility in labour markets. We conclude that the apparent duality -formal and informal- in the Argentinean labour market which seems to reflect differences in access to productive resources (human capital) outside labour market is the one that determines the integration into labour markets and later labour mobility of a big part of labour force.